The Eastern necropolis of Nea Paphos: overcoming challenges in a lost landscape - Lysandrou, Vasiliki; Agapiou, Athos; Michaelides, Demetrios; Papasavvas, George (My University, 2018)
This paper presents a multidisciplinary methodological approach to the study of archaeological sites with low visibility in the modern landscape. The urban expansion of many modern cities that have been developed very near or on ancient grounds has had a serious effect on the visibility of ancient sites. In addition, the unearthing of archaeological locales as a result of rescue excavations conducted by traditional means in the last hundred years and without the help of recent technological advances, also contributed to limited visibility of ancient sites on the modern landscape. This paper addresses this issue by focusing on an important archaeological site on the island of Cyprus, namely the Eastern necropolis of Nea Paphos, a significant funerary landscape in Hellenistic and Roman times. Rescue excavations back in the 1980s brought to light a plethora of burial architecture, of shaft and chamber tomb types. Despite detailed excavation records, information regarding the exact location and spatial distribution of these features is not available and is now lost forever since the modern city's urban expansion significantly altered the ancient landscape. The paper proposes a methodological approach to dealing with this issue that brings together traditional archaeological data, geo-data and modern geospatial tools. Even though the focus of this study is the Hellenistic-Roman necropolis of Nea Paphos in southwest Cyprus, the methodology could find wide application to low visibility archaeological sites throughout the island, especially where funerary landscapes are involved, excavated in the past under the form of rescue excavations.
Keywords: Hellenistic-Roman funerary landscape; Tomb architecture; Eastern necropolis of Nea Paphos; Legacy survey data; Cyprus